2023
DOI: 10.3389/fonc.2022.1007317
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of mixed neuroendocrine non-neuroendocrine neoplasms (MiNENs): A SEER database analysis of 767 cases

Abstract: BackgroundMixed neuroendocrine non-neuroendocrine neoplasm (MiNEN) is an extremely rare entity, consisting of neuroendocrine and non-neuroendocrine components. It can occur in various organs throughout the body, with a rising incidence. Its clinical management is a rapidly growing field of interest; however, large-scale patient cohorts are still missing to guide clinical practice.Patients and methodsThe demographic, clinicopathological, and survival information of all patients diagnosed with MiNEN in the natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…However, the bene t of surgical treatment for MANECs that have metastasised is unclear. A recent retrospective analysis suggests that only patients with metastatic MANECs from the appendix may bene t from surgical resection compared to other sites [23]. In terms of surgical method selection, Zhao, Bochao et al's study showed that for patients with appendiceal MANECs, regardless of lymph node metastasis, hemicolectomy has better survival bene ts than appendectomy (P<0.05) [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, the bene t of surgical treatment for MANECs that have metastasised is unclear. A recent retrospective analysis suggests that only patients with metastatic MANECs from the appendix may bene t from surgical resection compared to other sites [23]. In terms of surgical method selection, Zhao, Bochao et al's study showed that for patients with appendiceal MANECs, regardless of lymph node metastasis, hemicolectomy has better survival bene ts than appendectomy (P<0.05) [24].…”
Section: Discussionmentioning
confidence: 99%
“…The following inclusion criteria were used: (1) tumor histological type: MiNENs (SEER histology code: 8244/3)(Song et al 2022 ), and NETs (SEER histology codes: 8013/3, 8041/3, 8150/3–8157/3, 8240/3, 8241/3, 8242/3, 8243/3, 8246/3, 8249/3) (Cai et al 2022 ; Shah et al 2019 ; Miao et al 2018 ); (2) confirmation of MiNENs and NETs diagnosis histologically or microscopically. The following were the exclusion criteria: (1) survival time was unknown; (2) incomplete clinical and pathological data.…”
Section: Methodsmentioning
confidence: 99%
“…However, the adjuvant therapies for these two components are quite different ( 84 ). In addition, although a number of molecularly targeted drugs and immunotherapies have been initially used to treat MiNENs, evidence of efficacy is limited ( 1 , 85 , 86 ). Given that certain intermediate MiNENs frequently exhibit a significant presence of type 2 somatostatin receptors, it is plausible that patients with such conditions might potentially derive therapeutic benefits from the administration of long-acting somatostatin analogues and peptide-irradiated nucleotide treatment ( 56 ).…”
Section: Treatment Of Gastric Minensmentioning
confidence: 99%
“…A subgroup of gastric tumours known as g-MiNENs, or gastric mixed neuroendocrine-non-neuroendocrine neoplasms, is morphologically diverse and clinically aggressive. Most individuals with MiNENs are older than 50 years of age, and most MiNENs are discovered at an advanced stage of illness ( 1 ). As awareness of MiNEN increases and diagnostic techniques improve, the number of patients tends to increase ( 2 ).…”
Section: Introductionmentioning
confidence: 99%